FACTORS INFLUENCING ADOLESCENT EATING HABITS DURING THE NEW NORMAL ERA OF THE COVID-19 PANDEMIC IN DENPASAR CITY - Satiawati Kurnianingsih, I Desak Ketut Dewi; Batiari, Ni Made Padma; Oktavianti, Ni Kadek Rika (HEARTY, 2024)
The study aims to comprehend how the eating habits of school adolescents have changed during the adaptation period of the new normal of COVID-19, as well as to evaluate the relationship between adolescents' sociodemographic characteristics and learning methods in school with their eating habits. A cross-sectional quantitative study was conducted in Denpasar City with 352 adolescents aged 10-21 years, utilizing a questionnaire measuring eating habits based on the Adolescent Food Habits Checklist (AFHC). The research results indicate that factors such as age (OR=7.57; p<0.05), gender (OR=0.39; p<0.05), parental income (OR=1.83; p<0.05), and learning methods (OR=2.71; p<0.05) in school influence adolescent eating habits. Furthermore, the majority of adolescents (60%) exhibit poor eating habits, with a significant portion having suboptimal nutritional status, including 46.3% underweight, 11.1% at risk of overweight, and 3.4% classified as Obesity II. Therefore, collaboration among parents, schools, and health departments is essential to promote healthier eating patterns for adolescents.